1997
DOI: 10.1097/00004872-199715080-00009
|View full text |Cite
|
Sign up to set email alerts
|

Elevated blood pressure in spontaneously hypertensive rats consuming a high sucrose diet is associated with elevated angiotensin II and is reversed by vanadium

Abstract: That Ang II levels are elevated in sucrose-induced hypertension and decreased after vanadium therapy suggests that the renin-angiotensin system plays a role in the induction of hypertension in this model. On the other hand, the elevation of endothelin-1 levels associated with a decreased systolic blood pressure might be secondary to vanadium stimulation of endothelial cells. The data suggest that endothelin-1 is not involved in sugar-induced elevations of the blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…In addition to our finding of microvascular dysfunction and depressed NO signaling, sucrose-induced hypertension is related to other pathogenic factors including elevated plasma renin activity [73] and angiotensin II [74], peripheral sympathetic activation [75,76,77], and abnormal sodium and water homeostasis [78]. Whether these perturbations are influenced by dietary Cr 3 remains to be determined.…”
Section: Discussionmentioning
confidence: 87%
“…In addition to our finding of microvascular dysfunction and depressed NO signaling, sucrose-induced hypertension is related to other pathogenic factors including elevated plasma renin activity [73] and angiotensin II [74], peripheral sympathetic activation [75,76,77], and abnormal sodium and water homeostasis [78]. Whether these perturbations are influenced by dietary Cr 3 remains to be determined.…”
Section: Discussionmentioning
confidence: 87%
“…1). Since GSH was found to be involved in vanadate bioreduction [10][11][12][13][14][15], the levels of GSH should be affected when vanadate is administered. Indeed, it has been reported that the GSH pool is enhanced in the presence of vanadate [23,39].…”
Section: Resultsmentioning
confidence: 99%
“…Vanadium can induce the formation of reactive oxygen species (ROS) in biological systems through: (i) Fenton-like reactions [9]; (ii) vanadate bioreduction mediated by reduced glutathione (GSH), flavoenzymes or NAD(P)H oxidases with ROS as a by-product [10][11][12][13][14][15]; (iii) and recent evidences point out to an indirect promotion of ROS production, probably by interacting with mitochondria [16]. Moreover, vanadium toxicological effects in several cell types have been related with ROS production [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Several biological studies associate vanadium with the ability to produce reactive oxygen species (ROS) resulting in antioxidant enzymes alterations and leading to lipid peroxidation [1][2][3][4][5][6][7][8]. The involvement of toxic metals in cardiac oxidative damage suggests that this organ shows a great vulnerability to metal intoxication [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%